CONVECTIVE HEAT AND CASSON NANOFLUID FLOW OVER A VERTICAL PLATE WITH HEAT SOURCE (FUDMA JOURNAL OF SCIENCES, 2023)
This paper considers the Casson nanofluid flow of a free convective heat transfer with heat source over a vertical plate and its thermophysical properties. The governing partial differential equations were reduced to couple nonlinear ordinary differential equations using similarity variables. The couple nonlinear ordinary differential equations were solved numerically using Runge-Kutta fourth order method with shooting technique and implemented using MatLab. The effects of various non-dimensional governing parameter namely, Prandtl number, Biot number, Grashof number, heat source parameter, skin-friction coefficient, Nusselt number and Sherwood number is analysed for Casson nanofluid flow, discussed and presented graphically. The result showed that heat source parameter increases in skin-friction coefficient, velocity and temperature profiles but, decreases in concentration profiles and Nusselt number.
Keywords: Fluid flow; Nanoparticles; Sherwood number; Skin-friction coefficient; Thermophysical parameters; Vertical Plate